2008
DOI: 10.1055/s-0028-1085462
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Bilateral Perisylvian Syndrome: Familial Occurrence, Clinical and Psycholinguistic Aspects Correlated with MRI

Abstract: The severity of clinical manifestations in CBPS is correlated with the extent of cortical involvement. Most patients with CBPS have a history of speech delay or language difficulties and no epilepsy. Dyslexia can be found in patients with PMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
1
23
0
3
Order By: Relevance
“…Histologic characteristics of these malformations strongly suggested a genesis in prenatal development, since they revealed abnormal placement of neurons within cortical layers (i.e., malformations including ectopias and microgyria). More recently, similar findings have been reported for individuals with developmental language impairment (Oliveira et al, 2007; Brandão-Almeida et al, 2008; Boscariol et al, 2010, 2011). Initially, these findings were thought to implicate a relationship between clinical diagnosis and specific disruption of fronto-temporal regions critical to language processing (since the distribution of anomalies in the affected brains was substantially greater in left perisylvian areas).…”
Section: Auditory Processing Deficits and Language Disability: Human supporting
confidence: 78%
“…Histologic characteristics of these malformations strongly suggested a genesis in prenatal development, since they revealed abnormal placement of neurons within cortical layers (i.e., malformations including ectopias and microgyria). More recently, similar findings have been reported for individuals with developmental language impairment (Oliveira et al, 2007; Brandão-Almeida et al, 2008; Boscariol et al, 2010, 2011). Initially, these findings were thought to implicate a relationship between clinical diagnosis and specific disruption of fronto-temporal regions critical to language processing (since the distribution of anomalies in the affected brains was substantially greater in left perisylvian areas).…”
Section: Auditory Processing Deficits and Language Disability: Human supporting
confidence: 78%
“…The most consistent findings were ectopy and occasional microgyria, mainly affecting the perisylvian region of the left hemisphere4. Magnetic resonance imaging identified perisylvian polymicrogyria in families with histories of language and learning disabilities5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective (n=2) and prospective (n=4) cohort studies were identified, as well as two case-control studies. 16 Four studies only included participants with a primary presenting problem of language delay 19,28,29 or diagnosis of specific language impairment, 30 now referred to as developmental language disorder. 23 Four studies limited inclusion to participants with IQ/Performance IQ over 70 19,28 or 80, 29 or to individuals without cognitive impairment but did not define this according to a specific IQ.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…11 With advances in neuroimaging, confusion in terminology has arisen due to the multiplicity of terms used to describe what is now defined as BPP based on imaging findings. 16,17 Significant language delays and differences between receptive and expressive language scores have been noted in the WDS and congenital bilateral perisylvian syndrome populations. 5 While the term Foix-Chavany-Marie syndrome is typically associated with opercular infarcts, a developmental form has been described which is BPP.…”
mentioning
confidence: 99%
See 1 more Smart Citation